Edukasi Gizi dan Penguatan Penyelenggaraan Makanan Sekolah di SD Islam Budi Mulia Padang : Nutrition Education and Strengthening of School Meal Program Implementation at SD Islam Budi Mulia Padang - Resmiati Resmiati; Yeffi Masnarivan; Azrimaidaliza Azrimaidaliza; Nabiha Zaafarani (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2026)
Nutrition problems among primary school children remain an important public health concern, as they affect growth, learning concentration, and academic performance. Limited understanding of balanced nutrition and inadequate implementation of healthy school food services continue to be challenges in many educational institutions. This community engagement program aimed to improve students’ and teachers’ knowledge of balanced nutrition and to strengthen school food service implementation. Educational sessions were delivered to 59 fifth-grade students through interactive lectures and leaflets covering principles of balanced nutrition, the “Isi Piringku” concept, and food waste reduction. A module was also provided for teachers and the managing foundation to support the implementation and sustainability of the school food service program. Knowledge change was evaluated using pretest–posttest questionnaires. In addition, a qualitative assessment of the school food service implementation was conducted through discussions with teachers and school administrators to identify strengths and areas for improvement. The results indicated a 30% average increase in students’ knowledge about balanced nutrition, accompanied by improvements in their attitudes toward healthy eating practices. The program also enhanced teachers’ awareness of the importance of menu diversity and adherence to nutrition standards for school-aged children. The school principal also expressed commitment to communicating and following up on the recommendations with the foundation. This program contributed to strengthening nutrition literacy and improving the school food service system. The provision of a school food service module and educational materials is expected to support the sustainability of healthy school initiatives at SD Islam Budi Mulia Padang.